KERUGIAN EKONOMI PASIEN TUBERKULOSIS (TB) PARU SELAMA PERIODE KABUT ASAP DAN BUKAN KABUT ASAP DI KOTA PEKANBARU - Siska Finalita; Sukendi Sukendi; Suyanto Suyanto (Program Pascasarjana Universitas Riau, 2018)
This research was conducted from January to August 2018 and took place in 20 Pekanbaru health centers. The purpose of this study was to determine the conditions of air pollution based on PM10 parameters in Pekanbaru City in 2015 and to divide in periods of smog and not haze, the character of new pulmonary tuberculosis (TB) patients undergoing treatment during periods of smog and not smoke haze, expenditure released by the average of each new pulmonary TB patient in the period of smog and not smog and economic losses incurred by new pulmonary TB patients during the period of smog and not haze. The results of the study, months that exceed the quality standard PM10 in the air 150 µg / m3 are July, September and October. Smog period, May, June, July, August, September and October, not smoke haze January, February, March, April, November and December. The majority of those with new pulmonary TB treatment during the non-haze period, men (75.4%) p-value 0.885 and young age group (90.7%) p-values 0.335. The total direct cost of new pulmonary TB patients during smog is Rp. 2,230,000 (141.5,343.1) and as long as it is not smog Rp. 2,020,000 (125,347) with p-value 0.538. The highest expenditure is food costs (p-value 0.043) and mask costs (p-value <0.001). The total indirect cost of new pulmonary TB patients during the smog period is Rp. 1,600,000 (121,297) and not a smog period of Rp. 1,470,000 (45,266.2). Percentage of median total economic loss due to new pulmonary tuberculosis during 20.8% smog (14.6.31.8) and as long as it is not smog 19.5% (12.9, 33) with p-value 0.396.